KONTEKS KOMUNIKASI ANTARA GURU BK DAN SISWA TERHADAP PEMBENTUKAN SIKAP SOSIAL DI MADRASAH ALIYAH - Zahriyah, Sofiatus (LP2M Sekolah Tinggi Agama Islam Al Falah ( STAIFA ) Pamekasan, 2021)
Guidance and Counseling Teachers are the main elements in the implementation of guidance and counseling in schools that are responsible for forming the personalities of their students. Guidance and Counseling Teachers need a communication to students to channel their assignments. Communication is different between counseling teachers with subject teachers, guidance and counseling teachers have their own techniques or strategies in communicating with students so that how they can be accepted by these students. The research to find out about: 1) Factors that influence social attitudes in MA tarbiyatun Nasyiin 2) Application of the context of Guidance and Counseling teacher communication towards the Formation of Students' Social Attitudes in MA Tarbiyatun Nasyiin 3) Application of the Guidance and Counseling Teacher communication context towards the Establishment of Students Social Attitudes in MA tarbiyatun Nasyiin . This study uses qualitative research methods and the type of descriptive research is the data collected is in the form of words, images, and not numbers. This is caused by the application of qualitative methods. Besides all that is collected is likely to be the key to what has been researched.